2020
DOI: 10.1016/j.isci.2020.101408
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration-Based Patient-Derived Cancer Organoids

Abstract: Summary Patient-derived cancer organoids hold great potential to accurately model and predict therapeutic responses. Efficient organoid isolation methods that minimize post-collection manipulation of tissues would improve adaptability, accuracy, and applicability to both experimental and real-time clinical settings. Here we present a simple and minimally invasive fine-needle aspiration (FNA)-based organoid culture technique using a variety of tumor types including gastrointestinal, thyroid, melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 31 publications
0
59
0
Order By: Relevance
“…Between one to three weeks of culture, single cells and small clusters obtained from FNA grow to create small organoids ( Figure 4 ). Initial organoid culture success rates and long-term propagation rates following cryopreservation can be found in Vilgelm et al., 2020 .
Figure 4 Images of patient-derived cancer organoids (A) Bright-field images of patient-derived melanoma organoids plated in disc culture 6 days after plating 10×.
…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Between one to three weeks of culture, single cells and small clusters obtained from FNA grow to create small organoids ( Figure 4 ). Initial organoid culture success rates and long-term propagation rates following cryopreservation can be found in Vilgelm et al., 2020 .
Figure 4 Images of patient-derived cancer organoids (A) Bright-field images of patient-derived melanoma organoids plated in disc culture 6 days after plating 10×.
…”
Section: Expected Outcomesmentioning
confidence: 99%
“…Aspiration of core tissue with preserved architecture is also beneficial for diagnosis and obtaining a sufficient amount of sample for the organoid establishment and molecular genetic studies. The success rate of PDO establishment from tissues obtained through EUS-guided sampling is reported to be about 60% to 82% [ 61 , 62 , 70 , 71 , 72 , 73 , 74 ], which is the same success rate as with surgically resected tissues. Furthermore, there is no significant difference in the establishment efficiency between single-pass and double-pass punctures, therefore single-pass punctures with a 22-gauge FNB needle are recommended [ 74 ].…”
Section: Personalized Cancer Treatment Using Pharmacological Profimentioning
confidence: 99%
“…Access to primary tissue samples, including human tumors or those from animal models, is required for organoid derivation. Organoids are most easily generated from resection specimens due to the quantity of tissue available, but multiple recent studies have shown the feasibility of organoid generation from needle biopsies from some organs [49–51]. This flexibility in starting material is particularly important for tumor types in which neoadjuvant chemotherapy is commonly administered prior to surgery; derivation of organoids from needle biopsies allows culture and interrogation of treatment‐naïve organoids.…”
Section: How Can I Adapt Organoid Techniques For My Research Program?mentioning
confidence: 99%